PENGENDALIAAN PELAKSANAAN PROYEK KONSTRUKSIPADA PEMBANGUNAN BANGUNAN ATAS JEMBATAN BETON DENGAN KONSEP NILAI HASIL (EARNED VALUE CONCEP) - Ketut Nudja (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2017)
ABSTRACT Cost control is the heart of activities for contractors, because from this methode the company can earn profit and reduce the risk. Project managers must undertake project controls by "entrepreneurial spirit" or entrepreneurial spirit, so the work value shown, not the "intelligence of speech". The purpose of controlling the implementation of construction projects on "Building Construction on Concrete Bridges" is to be able to know whether the implementation in accordance with the design that has been set, so useful to be able to reduce the occurrence of undesirable irregularities. The result shown until the 8th week (when evaluated), it is found that the Schedule Variance (SV) Value is Rp. (293,892,353.04), this is SV